Investigating the inflammation marker neutrophil-to-lymphocyte ratio in Danish blood donors with restless legs syndrome - Joseph Dowsett (Public Library of Science (PLoS), 2021)
Background Restless Legs Syndrome (RLS) is a neurological sensorimotor disorder that occurs in the evening and night, thereby impacting quality of sleep in sufferers. The pathophysiology of RLS is poorly understood but inflammation has been proposed as possibly being involved. The neutrophil-to-lymphocyte ratio (NLR) can be used as an inflammation marker but results from small studies have been inconclusive in determining whether NLR is associated with RLS. We aimed to assess whether an association between NLR and RLS exists in a large cohort of healthy individuals. Methods Neutrophils and lymphocytes were measured in blood samples of 13,055 individuals from the Danish Blood Donor Study, all of whom completed the validated Cambridge-Hopkins RLS-questionnaire for RLS assessment. Results In the sample, 661 individuals were determined as current RLS cases (5.1%). A higher proportion of individuals with RLS were females (62.5% vs 47.5%; P<0.001) and RLS cases were older than controls (P<0.001), but no differences in body mass index (BMI), smoking or alcohol consumption were found between the two groups. An increased NLR was observed in RLS cases compared to controls (median NLR: 1.80 vs 1.72; P = 0.033). In an unadjusted logistic regression model, increased NLR was associated with RLS (OR = 1.10 per NLR unit increase [95%CI:1.01–1.20]; P = 0.032); however, the association was not significant in multivariate models adjusting for sex and age (P = 0.094) or sex, age, alcohol consumption, smoking status and BMI (P = 0.107). Conclusion We found no association between RLS and NLR among Danish blood donors after adjusting for sex, age, alcohol consumption, smoking status and BMI. Further studies are needed to determine whether inflammation is a risk factor for RLS.